JUAL BELI TERNAK DENGAN KAIN PENUTUP: ANALISIS BUDAYA DAN EKONOMI DI PASAR TERNAK MUARO PANEH SOLOK - Kori, Kori Lilie (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Abstract This article examines the phenomenon of buying and selling livestock carried out at the Muaro Paneh Solok Livestock Market, with a focus on the practice of livestock trading using a unique method during transactions, namely when haggling over prices between buyers and sellers using cloth coverings and finger symbols to determine the price. livestock, so no one knows how much livestock prices are offered by sellers to buyers. The culture of transactions using cloth coverings is a tradition carried out by the local community with the aim of establishing an attitude of mutual care and respect for fellow traders. This is one of the local wisdoms found in the Muaro Paneh livestock market, Bukit Sundi sub-district, Solok regency. This research aims to analyze the cultural and economic aspects of this practice as well as the relevance of this tradition in the lives of local communities. Using a qualitative approach and participant observation, this research found that the use of cloth coverings in livestock transactions not only has economic value, but also reflects rich social, symbolic and cultural dimensions in social interactions between sellers and buyers. The results of the analysis show that the cloth covering is not only a transaction tool, but also a symbol that contains deep religious and social meaning.